Vicente Krause - Chescotta, Jorge; Argüello, Alejandro; Lilli, Pablo Félix; Sánchez, Jorge Alberto
El artículo realiza un homenaje al arquitecto Vicente Krause con relatos de varios de sus colegas.
Keywords: ARQUITECTOS; BIOGRAFIAS; KRAUSE, VICENTE; FAU